Medical staff morality - Litvak, A. I.; Mykhaylenko, V. L.; Fedorchenko, R. A.; Литвак, А. І.; Михайленко, В. Л.; Федорченко, Руслана Анатоліївна (My University, 2020)
The medical help is considered to be full when medical staff not only use medical and diagnostic technology properly, but also follow the ethical rules. The research showed questionnaire to be a good method of diagnostic for both medical staff ethical potential and the individual employee's one. The scale for assessing group ethical preferences is considered to be effective also. The data resulted in a high level of ethical values and behaviour for only every eleventh respondent include. The majority of respondents, more than two-thirds, showed an average level and one of five - showed a low ethical level, mainly due to the low ethics of males. The ethical learning is an urgent and indispensable task of the medical environment in public professional organizations. The ethical trainings for different social groups (as males, females doctors and the medical staff) should be distinctively different in content and occurred in each medical organisation annually. The medical ethics has become a professional competence factor of medical staff and it should be taken care of, both the public and administrators, heads of medical institutions at all levels of government. Вважається, що медична допомога повноцінна тоді, коли медичний персонал додержується усіх етичних норм і правил, а не тільки правильно і адекватно використовує лікувально-діагностичну технологію. Дослідження показало результативність використання анкетування, як засобу діагностики рівня етичного потенціалу медичного закладу і окремого співробітника, а також запропоновану шкалу оцінки групових етичних уподобань. За результатами дослідження тільки кожен одинадцятий респондент показав високий рівень етичних цінностей і поведінки. Найбільша частина людей – більш як дві третини, показали середній рівень і кожен п’ятий респондент продемонстрував низький рівень етичності, головним чином, за рахунок низької етичності чоловіків. Навчання етичним правилам, нормам і поведінки є невідкладним і неодмінним завданням лікарського середовища, громадських професійних організацій. Етичні тренінги для різних соціальних груп (лікарів чоловіків, жінок і середнього медичного персоналу) за змістом мають суттєво відрізнятися і відбуватися в кожній медичній організації, хоча б раз на рік. Можна стверджувати, що медична етика стала фактором професійної компетентності медичного персоналу і нею слід опікуватися, як громадськості, так і адміністраторам, керівникам медичного закладу на всіх рівнях управління.
Моральність медичного персоналу
Keywords: morality; medical staff; questionnaire; doctors; nurses; women; men; ethical level